Surgical technologies of sutured iris fixation of the dislocated IOL — fibrosed capsular bag complex - V. N. Nikitin; D. I. Ivanov (Российский офтальмологический журнал)
Purpose. To present various techniques of surgical treatment with the dislocation of the IOL — fibrosed capsular bag complex, and to analyze their clinical and functional results.Material and methods. 50 patients (mean age 75.7 ± 1.3 years) who received surgery with IOL-capsular bag complex (ICBC) were divided into 2 groups according to the applied treatment tactics. Tactics 1 consisted in suturing ICBC to the iris on the support needle without manipulations with the capsular bag (26 eyes). Tactic 2 involved IOL suturing to the iris in combination with various manipulations on the capsular bag, aimed at partial or complete removal of fibrous tissue (24 eyes). The follow-up period ranged from 4 to 6 years.Results. The criteria affecting the choice of the treatment technique were determined: integrity of the Zinn ligament, manifestation of capsular bag fibrosis (phimosis of the anterior capsulorhexis, fibrosis of the posterior capsule); impact of changes in the capsular bag structure on the correct position of the IOL (frontal inclination of the IOL, inversion of haptic elements to the optic zone); presence of a prolapse of the vitreous body; Semmering's ring with a high risk of the release of lens masses. A frequency occurrence analysis of the proposed criteria showed their importance in the choice of surgical treatment technique in patients with mixed type ICBC dislocation. Remote functional results of the operations are presented.Conclusion. The proposed low invasive methods of surgical treatment of patients with the dislocation of the IOL — fibrosed capsular bag complex are reliable and technically simple. Relative indications to choosing the treatment method with dislocation of the IOL-fibrosed capsular bag complex have been determined for various combinations of the proposed criteria.